Evolutionary Basis for the Coupled-domain Motions in Thermus thermophilus Leucyl-tRNA Synthetase - Weimer, Kristina Mary Ellen (American Society for Biochemistry and Molecular Biology, 2009)
Aminoacyl-tRNA synthetases are multidomain proteins that catalyze the covalent attachment of amino acids to their cognate transfer RNA. Various domains of an aminoacyl-tRNA synthetase perform their specific functions in a highly coordinated manner to maintain high accuracy in protein synthesis in cells. The coordination of their function, therefore, requires communication between domains. In this study we explored the relevance of enzyme motion in domain-domain communications. Specifically, we attempted to probe whether the communication between distantly located domains of a multidomain protein is accomplished through a coordinated movement of structural elements. We investigated the collective motion in Thermus thermophilus leucyl-tRNA synthetase by studying the low frequency normal modes. We identified the mode that best described the experimentally observed conformational changes of T. thermophilus leucyl-tRNA synthetase upon substrate binding and analyzed the correlated and anticorrelated motions between different domains. Furthermore, we used statistical coupling analysis to explore if the amino acid pairs and/or clusters whose motions are thermally coupled have also coevolved. Our study demonstrates that a small number of residues belong to the category whose coupled thermal motions correspond to evolutionary coupling as well. These residue clusters constitute a distinguished set of interacting networks that are sparsely distributed in the domain interface. Residues of these networking clusters are within van der Waals contact, and we suggest that they are critical in the propagation of long range mechanochemical motions in T. thermophilus leucyl-tRNA synthetase.